Correlates of Lifetime and Past Month Vape Use in a Sample of Canadian University Students - Jamie A Seabrook; Jasna Twynstra; Jason A Gilliland (SAGE Publishing, 2021)
Introduction: This study examines correlates of lifetime (ie, ever vaped) and past month vape use among students aged 17 to 19 years, 20 to 25 years, and 26+ years from Western University in London, Ontario. The secondary objective is to assess lifetime and past month vape use among students not of legal age to purchase vaping products in Ontario (ie, those 17 to 18 years only). Methods: Using Qualtrics, a cross-sectional survey was sent via email to all students at Western University (N = 38 442), assessing their current and past risk-taking behaviors, mental health, sociodemographic characteristics, as well as questions pertaining to their family structure and socioeconomic background during childhood. Students were asked if they had ever vaped in their lifetime and about past month vape use. Logistic regression models were used to assess correlates of lifetime and past month vape use. Results: The sample consisted of 2626 university students. Compared to those ages 26+ years, teenage university students were 10 times more likely to have vaped in the past month and males were twice as likely as females to have vaped. Alcohol use doubled the odds of vaping in the past month, whereas cigarette, cannabis, or cocaine use approximately tripled the odds. Students who reported many sexual partners were far more likely to have vaped in the past month. Conclusion: Vape use is more common among teenage university students, males, those who drink alcohol, smoke, use cannabis or cocaine, and who report many sexual partners.